BET-Inhibitors Disrupt Rad21-Dependent Conformational Control of KSHV Latency - Chen, Horng-Shen (PLoS Pathog, 2017)
Kaposi’s Sarcoma-associated Herpesvirus (KSHV) establishes stable latent infection in B-lymphocytes and pleural effusion lymphomas (PELs). During latency, the viral genome persists as an epigenetically constrained episome with restricted gene expression programs. To identify epigenetic regulators of KSHV latency, we screened a focused small molecule library containing known inhibitors of epigenetic factors. We identified JQ1, a Bromodomain and Extended Terminal (BET) protein inhibitor, as a potent activator of KSHV lytic reactivation from B-cells carrying episomal KSHV. We validated that JQ1 and other BET inhibitors efficiently stimulated reactivation of KSHV from latently infected PEL cells. We found that BET proteins BRD2 and BRD4 localize to several regions of the viral genome, including the LANA binding sites within the terminal repeats (TR), as well as at CTCF-cohesin sites in the latent and lytic control regions. JQ1 did not disrupt the interaction of BRD4 or BRD2 with LANA, but did reduce the binding of LANA with KSHV TR. We have previously demonstrated a cohesin-dependent DNA-loop interaction between the latent and lytic control regions that restrict expression of ORF50/RTA and ORF45 immediate early gene transcripts. JQ1 reduced binding of cohesin subunit Rad21 with the CTCF binding sites in the latency and lytic control regions. JQ1 also reduced DNA-loop interaction between latent and lytic control regions. These findings implicate BET proteins BRD2 and BRD4 in the maintenance of KSHV chromatin architecture during latency and reveal BET inhibitors as potent activators of KSHV reactivation from latency.